Evolutionary governance in China: state-society relations under authoritarianism - Chung, Yousun (Harvard contemporary China series, 2021)
""Adopts an evolutionary framework to examine how the Chinese state relates with non-state actors across several fields of governance: community, environment, public health, economics, labor, society, and religion; identifies areas where state-society interactions have shifted over time, ranging from constructive engagement to protracted conflict, thereby providing nuanced insight into the circumstances wherein the party-state exerts its coercive power versus engaging in more flexible responses"--Provided by publisher"--